Surveillance for Risk Factors of Surgical Site Infection after Cesarean Section, A Hospital Setting in Lasinrang Indonesia: A Prospective Cohort Study - Natsir, Nurhidayah; Masriadi, Masriadi; Samsualam, Samsualam (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Infection is the most common cause of mortality and morbidity in pregnant women during cesarean section. Hence this study was undertaken to study surveillance of SSI after cesarean section at surveillance risk factors for Surgical Site Infection (SSI) after cesarean section. The purpose of this research was to know the ASA score, obesity, duration of operation, type of surgery, wound classification, and prophylaxis are the risk factors surgical site infections. This type of research is the observational research by using a prospective cohort study design. Total sample that would be analysis in this study was 88 samples. The data were processed using univariate, bivariate and multivariate analysis. The results showed that ASA score exponent (B) (estimate odds ratio) ASA score 23 and wound classification 7.667 collectively to wound condition of patients operation with cesarean section with p-value = 0.005. ASA scores have the greatest risk of incidence of cesarean section wound infection. Keywords: Surveillance, Cesarean section, Infection, Surgical site, Indonesia